EVALUASI PEMANFAATAN PUPUK ORGANIK CAIR DENGAN STARTER ECO-FARMING PADA USHATANI SAWI DI DESA BUG-BUG KECAMATAN LINGSAR - Tajidan, Tajidan; Halil, Halil; Sukardi, Lalu; Sjah, Taslim; Jinem, Suparmin (Jurnal Pepadu, 2024)
Community service activities (PKM) are beneficial if the PKM work is implemented by partners. Therefore, after the PKM activities have passed, it is necessary to evaluate the use of liquid organic fertilizer with eco-farming starter (POC). The aim of this evaluation is to determine the extent to which POC fertilizer is used in increasing production, production value and performance of caisim mustard plants in farming in Bug-bug Village, Lingsar District. The evaluation technique applied in evaluating PKM implementation is the tiling technique. The tiles measure 100cm x 100cm consisting of 2 (two) tiles using POC and 2 (two) tiles without using POC. The evaluation results show that the use of POC is still applied by 60% of the total number of PKM participants and can increase production and production value by 26.67%, and an incremental benefit cost ratio value of 12.47 is obtained, meaning that the use of POC can attract farmers' interest in implementing it, because can increase production value.